Complementary Vantage Points: Integrating Hydrology and Economics for Sociohydrologic Knowledge Generation. Issue 4 (30th April 2019) - Müller, Marc F.; Levy, Morgan C.
Abstract: Because human and environmental systems in the Anthropocene are increasingly coupled, hydrologists and economists often find themselves studying the same systems from different vantage points. Here we argue that synthesis across economics and hydrology can help address two pressing sociohydrologic challenges: actionable prediction and the generation of transferable knowledge from place‐based studies. Specifically, we review (1) empirical methods and (2) theoretical approaches from economics and connect the two through a proposed iterative framework. First, we find that empirical methods for statistical analysis of natural and quasi‐experiments in economics can be leveraged to distinguish causal relations from mere correlations in complex and data scarce systems, which can help address the challenge of sociohydrologic prediction. Second, we find that economic theories based on rational choice can be used to decipher known paradoxes in water resources, which can help address the challenge of sociohydrologic knowledge generation. In both empirical and theoretical domains, specialized knowledge in hydrology remains critical to properly applying techniques from economics to coupled human‐water systems. We propose that linkages between the two fields highlight a large potential for interaction. Key Points: Hydrology and economics are complementary and compatible approaches to predict and understand sociohydrologic systems Econometric methods can be leveraged for quantitative causal inference from scarce observational data in coupled human‐water systems Integrating rational choice into sociohydrologic models can capture strategic behavior and explain water resources paradoxes